Pelarutan emas pada pelindian konsentrat emas hasil roasting menggunakan reagen tiosianat - Fika Rofiek Mufakhir; Jones Maima Sinaga; Soesaptri Oediyani; Widi Astuti (Jurnal Rekayasa Proses, 2019)
Dissolution of gold from roasting concentrate of gold ore using potassium thiocyanate with the presence of ferric chloride as an oxidizer was investigated. The concentrate was taken from Lengkukai gold mine. Gold ore particles under 53 µm in size were roasted at varied temperature, separated using wet magnetic separator, and finally leached. The X-ray diffraction (XRD) analysis showed that there were phase changes after roasting with the emergence of new phases such as hematite, pyrrhotite, and almandine. Leaching of gold concentrate after roasting and magnetic separation showed that gold was in non-magnetic concentrate at 950oC with the highest gold dissolution of 0.95 mg/L, while magnet concentrate was completely absent. Experiments with the addition of Fe3+ ion oxidizers for 24-hour range did not have significant effect on gold dissolution. The highest gold concentration obtained of 2.29 mg/L was obtained at 12 hours with 0.1 M FeCl3. The increase of thiocyanate reagent concentrations, which showed a linear correlation to gold dissolution, produced up to 2.25 mg/L of gold concentration (12 hours at 0.3 M KSCN).